The dilemma of improving rational antibiotic use in pediatric community-acquired pneumonia - Nguyen, Phuong T. K.; Robinson, Paul D.; Fitzgerald, Dominic A.; Marais, Ben J. (Frontiers in Pediatrics, 2023)
Pneumonia is the number one reason of disease and deaths in children under five years old, outside the neonatal period, with the greatest number of cases reported from resource-limited settings. The etiology is variable, with not much information on the local etiology drug resistance profile in many countries. Recent studies suggest an increasing contribution from respiratory viruses, also in children with severe pneumonia, with an increased relative contribution in settings that have good vaccine coverage against common bacterial pathogens. Respiratory virus circulation was greatly reduced during highly restrictive measures to contain the spread of COVID 19 but rebounded once COVID-19 restrictions were relaxed. We conducted a comprehensive literature review of the disease burden, pathogens, case management and current available prevention of community acquired childhood pneumonia, with a focus on rational antibiotic use, since the treatment of respiratory infections is the leading cause of antibiotic use in children. Consistent application of revised World Health Organisation (WHO) guidance that children presenting with coryzal symptoms or wheeze can be managed without antibiotics in the absence of fever, will help to reduce unnecessary antibiotic use, as will increased availability and use of available inflammatory markers at bed side such as C–reactive protein (CRP) in children with respiratory symptoms and fever.